Adaptability and Self-Organization of the Doctoral Training System - T. A. Starshinova (Moscow Polytechnic University, 2022)
Training of highly qualified personnel for science, education and industry is an important factor in the formation of a high-tech economy. The modern system of doctoral training does not always cope with its tasks. Enhancing the efficiency of doctoral training can be associated with an increase in adaptability and self-organization. The adaptation of the pedagogical system to changing conditions should be considered in a broad sense, while its fitting to students' features is a special manifestation of this property. It is necessary to work out two mechanisms of its adaptation - passive and active. Passive adaptation means adjusting to changing external conditions (including a new law), changing in the systems of an adjacent and higher levels. Active adaptation involves the influence on other subsystems of the university educational environment, such as master's school, additional education (retraining and advanced training of professors), the scientific and pedagogical personnel attestation system (dissertation councils), research departments. Such adaptation can take place according to the model of expanding influence, simultaneously at two levels - personal (subject-subjective) and organizational and managerial. Self-organization is considered as one of the most important features of the system adaptability and a condition for its successful functioning.